Recent advances in organic donor-acceptor cocrystals: design, synthetic approaches, and optical applications - Liu, Hui-Ying; Li, Ya-Cheng; Wang, Xue-Dong (CrystEngComm, 2023)
Organic donor-acceptor (D-A) cocrystals have recently attracted widespread attention owing to the synergetic electron donor-acceptor blending properties via non-covalent interactions, becoming good candidate materials for optoelectronic applications. However, the rational design and selection of donor/acceptor components in organic cocrystals with the desired morphology, size, and function remains a key synthetic objective. As the single components possess inherent individual properties, including optical, electronic, and crystalline lattice features, co-crystalline engineering is a powerful but challenging strategy for obtaining new materials with combined physical and chemical properties. In this review, we mainly focus on the organic donor acceptor cocrystal molecular design, synthetic approaches, and their photophysical and photochemical properties as well as optical function application devices. Finally, an outlook is provided for the future development of organic D-A cocrystals toward next-generation organic crystal materials. The recent progress in optical applications of organic donor-acceptor co-crystals is reviewed in terms of material design, synthetic approach and future perspectives.